Researching experiences of skin cancer patients: An intersubjective reflexive exploration of learning to feel comfortable in my ‘skin’ as a practitioner-researcher - Swales, Nicola (European Journal for Qualitative Research in Psychotherapy, 2023)
This paper offers two parallel explorations: The first is an expression of my experience into becoming “seen” as a practitioner-researcher and learning to feel comfortable in my “skin” as I journey from being a novice researcher to becoming a researcher and academic. The second exploration is the story of my unfolding PhD research which aimed to explore skin cancer patients experiences of the helpful factors of psychotherapy using constructivist grounded theory (CGT). Looking through the lens of autoethnography and reflexivity, I share the birth of my research using extracts and reflective commentary of my data via CGT memo-ing. I aim to explicate my experience of “imposter syndrome” and shame, as well as how I became emotionally entangled within an intersubjective reflexive process during data gathering. Here, vulnerable parts of myself were exposed along with parallels with my co-researchers (participants).